Pengaruh Media Sosial, Skin Health Awareness, Brand Preference, dan Kualitas Produk terhadap Pembelian Produk Skincare - Sifa Fauziah; Andri Kusmayadi (GEMILANG: Jurnal Manajemen dan Akuntansi, 2026)
The growth of the skincare industry in Indonesia continues to show an upward trend in line with increasing public awareness of the importance of maintaining healthy skin. This study aims to examine the influence of social media, skin health awareness, brand preference, and product quality on the purchase decisions of skincare products in the Greater Jakarta area. A quantitative approach was employed through the distribution of online questionnaires to 125 respondents who actively use social media. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method version 4.0. The findings indicate that all four variables have a positive and significant effect on purchase decisions, with product quality being the most dominant factor, followed by skin health awareness, social media, and brand preference. This study suggests that companies should improve product quality, build brand trust, and optimize digital communication. The findings not only provide practical contributions for industry players in designing marketing strategies but also broaden the understanding of consumer behavior, which is increasingly influenced by skin health awareness in making skincare product choices.